Enhancing Administrative Competencies through Productivity `Technology and Artificial Intelligence (AI) Integration in Muhammadiyah Elementary Schools, Bantul - Cepi Safruddin Abdul Jabar; Wiwik Wijayanti; Tina Rahmawati; Rahmania Utari; Widia Murni Wijaya (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Muhammadiyah Elementary Schools in Bantul face significant challenges in adopting productivity technologies and artificial intelligence (AI) for administrative tasks due to limitations in staff knowledge, infrastructure, and concerns about data security. To address these issues, a Community Service Program (PkM) was implemented to enhance administrative staff competencies through targeted training and mentoring. The program, conducted from June 13 to 20, 2024, at SD Muhammadiyah Tamantirto, involved 29 participants. It featured seminars, practical training, and hands-on mentoring focused on the application of productivity tools and AI in administrative workflows. Key activities included website development, data organization, and practical skill-building sessions, reinforced by pre-tests, post-tests, and participant satisfaction surveys to evaluate learning outcomes. The program successfully improved participants' ability to utilize modern technologies, fostering innovation and increasing administrative efficiency within the schools. The initiative highlights the potential for structured training and mentoring programs to overcome barriers to technology adoption in educational settings, contributing to the overall quality of school management and service delivery.